Kadar Lemak dan Air Pada Cookies dengan Substitusi Tepung Ubi Ungu dan Kacang Tanah - Nadia Karomatul Izza; Nanik Hamidah; Yahmi Ira Setyaningrum (Universitas Muhammadiyah Semarang, 2019)
Cookies are crispy textured cakes. The main ingredient used to make cookies is wheat flour. Substitution of flour with purple sweet potato is done because purple sweet potato has content such as wheat flour. Purple yam flour contains amylose of 24.79% and amylopectin of 49.78%.This research was conducted to analyze on fat level and water content in cookies. The study design was a Randomized Block Design. The treatment level was divided into 4 groups with the proportion of purple sweet potato flour: F0 (0%: 0%), F1 (55%: 20%), F2 (45%: 30%), and F3(35%: 40 %). Fat content analysis used was the soxhlet method. There was a significant effect (ρ = 0,000) on the amount of fat content in cookies. The highest fat content found in F3 was 38.85%.Water content analysis used was the Thermogravimetric method. Statistical analysis of water content using friedmen with a reliability level of 95%. There was a significant effect (ρ = 0,000) on the amount of water content in cookies. The lowest water content was in F3 of 38.85%. The higher the addition of peanut flour, the lower the water content of cookies. Keywords: Cookies, Purple Sweet Potatoes, Ground Peanuts, Fat Levels, Water Content